Answer: When the addition of two or more equations leads to the elimination of one of the variables.
Explanation:
When we have a system of equations, the addition method seems to be useful only when adding the equations will lead to the elimination of one of the variables:
An example of this can be, for the variables x and y:
3*x + x*y - 2*y = 3
x^2 + x*y - 2y = 42
now we can "add" (actually subtract) the equations and get (eq2 minus eq1)
(x^2 + x*y - 2y) - (3*x + x*y - 2*y ) = 42 - 3
x^2 - 3*x = 39
x^2 - 3*x - 39 = 0
And now we can solve it for x, and then find the value of y.